Development of a Knee Arthroplasty Episode-Based Cost Measure for Evaluating Cost in the Merit-Based Incentive Payment System. (5th January 2022) - Choradia, Nirmal; Lam, Joyce; Luo, Binglie; Bounds, Sam; Yates, Adolph J.; Quintana, Juan; Do, Rose; Feinberg, Laurie; Sandhu, Alex; Vail, Daniel; MaCurdy, Tom; Nagavarapu, Sriniketh; et al.
Abstract : Background: Under the Merit-based Incentive Payment System (MIPS), the U.S. Centers for Medicare and Medicaid Services (CMS) evaluate clinicians who manage Medicare patients on the basis of cost and quality outcomes. CMS contractor Acumen, LLC, convened an expert panel to develop a knee arthroplasty episode-based cost measure (EBCM) for use in the MIPS. Methods: A Clinical Subcommittee of 28 clinician experts affiliated with 27 specialty societies provided guidance in developing the knee arthroplasty EBCM. The Clinical Subcommittee specified all aspects of the EBCM including triggering of the episode, services within the episode, risk adjustment, subgrouping, and exclusions. Services were counted only if the Clinical Subcommittee deemed them under the influence of the clinician assigned to the EBCM (selective service assignment; SSA). We assessed the reliability of the EBCM and compared it with an alternative population-based cost measure constructed without SSA. Results: We identified 249, 301 knee arthroplasty episodes from June 1, 2016, to May 31, 2017, with 10, 681 clinicians having at least 10 attributed episodes. The mean episode cost was $19, 321 with a standard deviation of $1, 816. SSA increased the reliability score from 0.71 to 0.81 relative to an alternative measure that counted all patient costs. SSA also led to reclassification of 41.8% of clinicians into different quintiles of performance. Conclusions: We found that the use of SSA in the creation of the EBCM substantially reduces random noise (i.e., unrelated medical procedures or costs) and offers a tool for assessing clinicians' costs of management that is focused on care directly related to knee arthroplasty.